(untitled) (Journal of Parents and Teachers, 2013)
Videogames constitute an entertainment which children and young people spend much time with and from which they know and build the reality. Recognizing the positive aspect of them, the author wants to attract attention over the negative aspect, especially over the themes that she considers little suitable. She concludes recommending parents and teachers to be conscious of this reality and to act cautiously.